Whole-Plant Dynamic System of Nitrogen Use for Vegetative Growth and Grain Filling in Rice Plants (Oryza sativa L.) as Revealed through the Production of 350 Grains from a Germinated Seed Over 150 Days: A Review and Synthesis - Yoneyama, Tadakatsu; Tanno, Fumio; Tatsumi, Jiro; Mae, Tadahiko (Frontiers in Plant Science, 2016)
A single germinated rice (Oryza sativa L) seed can produce 350 grains with the sequential development of 15 leaves on the main stem and 7 ‒ 10 leaves on 4 productive tillers (forming 5 panicles in total), using nitrogen (N) taken up from the environment over a 150-day growing season. Nitrogen travels from uptake sites to the grain through growing organ-directed cycling among sequentially developed organs. Over the past 40 years, the dynamic system for N allocation during vegetative growth and grain filling has been elucidated through studies on N and 15N transport as well as enzymes and transporters involved. In this review, we synthesize the information obtained in these studies along the following main points: (1) During vegetative growth before grain-filling, about half of the total N in the growing organs, including young leaves, tillers, root tips and differentiating panicles is supplied via phloem from mature source organs such as leaves and roots, after turnover and remobilization of proteins, whereas the other half is newly taken up and supplied via xylem, with an efficient xylem-to-phloem transfer at stem nodes. Thus, the growth of new organs depends equally on both N sources. (2) A large fraction (as much as 80%) of the grain N is derived largely from mature organs such as leaves and stems by degradation, including the autophagy pathway of chloroplast proteins (e.g., Rubisco). (3) Mobilized proteinogenic amino acids, including arginine, lysine, proline and valine, are derived mainly from protein degradation, with amino acid transporters playing a role in transferring these amino acids across cell membranes of source and sink organs, and enabling their efficient reutilization in the latter. On the other hand, amino acids such as glutamine, glutamic acid, γ-amino butyric acid, aspartic acid, and alanine are produced by assimilation of newly taken up N by roots and transported via xylem and phloem. The formation of 350 filled grains over 50 days during the reproductive stage is ascribed mainly to degradation and remobilization of the reserves, previously accumulated over 100 days in the sequentially-developed vegetative organs.